Q. Simplify to create an equivalent expression.4(−15−3p)−4(−p+5)Choose 1 answer:(A) −8p−80(B) −13p−80(C) −8p+80(D) 8p−80
Distribute 4 into the first term: First, distribute the 4 into the parentheses in the first term 4(−15−3p).Calculation: 4×−15=−60 and 4×−3p=−12p.So, 4(−15−3p) becomes −60−12p.
Distribute −4 into the second term: Next, distribute the −4 into the parentheses in the second term −4(−p+5).Calculation: −4⋅−p=4p and −4⋅5=−20.So, −4(−p+5) becomes 4p−20.
Combine the results of distribution: Now, combine the results of the distribution from both terms.We have −60−12p from the first term and 4p−20 from the second term.Combining these gives us: −60−12p+4p−20.
Simplify the expression: Simplify the expression by combining like terms.The p terms: −12p+4p=−8p.The constant terms: −60−20=−80.So, the simplified expression is −8p−80.